(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article includes a wide group of game pedagogical technology, its techniques and methods. Also, a certain activity of the teacher: selection, development, preparation of games; involving children in play activities; implementation of the game itself; Processes such as summarizing the results of game activities are covered.